INTEGRATING FAITH WITH GLOBAL COMPETENCE IN PESANTREN ENGLISH EDUCATION: CHALLENGES AND STRATEGIES - Sari, Dhian Marita; Alsulami, Naif Daifullah (Edukasi Islami : Jurnal Pendidikan Islam, 2026)
The integration of English language education into Islamic boarding schools presents both pedagogical opportunities and ideological tensions. While English enables access to global knowledge and intercultural engagement, its incorporation into faith-based institutions raises concerns regarding identity preservation and cultural authenticity. This qualitative study investigates how English education is conceptualized, implemented, and experienced within a pesantren context. Drawing on interviews with leaders, teachers, and students, classroom observations, and document analysis, the study reveals an emerging integrative model in which English is reframed as a vehicle for da’wah, intellectual expansion, and global participation. Findings indicate that English is not positioned as a secular intrusion but as a strategic instrument embedded within Islamic epistemology. However, structural constraints including limited instructional time, technological resources, and curriculum coherencecomplicate sustainable implementation. The study proposes a Faith-Integrated Global Competence Model, demonstrating how religious identity, pedagogical practice, and institutional adaptation interact dynamically. This study contributes to the discourse on integrating global competencies with faith-based education, offering a contextual model for English language education that blends Islamic principles with global engagement.